Conservation of the Notch antagonist Hairless in arthropods: functional analysis of the crustacean Daphnia pulex Hairless gene. - Zehender, A.; Bayer, M.; Bauer, M.; Zeis, B.; Preiss, A.; Maier, D. (Development genes and evolution, 2017)
The Notch signaling pathway is highly conserved in all animal metazoa: upon Notch receptor activation, transcription of Notch target genes is turned on by an activator complex that centers on the transcription factor CSL. In the absence of signal, CSL assembles transcriptional repression complexes that display remarkable evolutionary diversity. The major antagonist of Notch signaling in insects named Hairless was originally identified in Drosophila melanogaster. It binds to the Drosophila CSL homologue Suppressor of Hairless [Su(H)] and recruits the two general co-repressors, Groucho and C-terminal binding protein. Whereas the majority of Notch signaling components is conserved between insects and vertebrates, Hairless is found only in insects. Here, we present the analysis of the Hairless gene from Daphnia pulex and, hence, for the first time from a crustacean. Daphnia and Drosophila Hairless protein sequences are highly diverged. Known functional domains, however, the Su(H), Groucho and the C-terminal binding protein interactions domains, are well conserved. Moreover, direct binding of the Daphnia Hairless protein and the respective Drosophila interaction partners was detected, demonstrating the conservation at the molecular level. In addition, interaction between Daphnia Hairless and Drosophila Su(H) was demonstrated in vivo, as co-overexpression of the respective genes during Drosophila development resulted in the expected downregulation of Notch activity in the fly. Structural models show that the Hairless-Su(H) repressor complexes from Daphnia and Drosophila are almost indistinguishable from one another. Amino acid residues in direct contact within the Hairless-Su(H) complex are at absolutely identical positions in the two homologues.